2020
DOI: 10.3390/ijerph18010059
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the COVID-19 Event on Deviant Workplace Behavior Taking Tianjin, Beijing and Hebei as an Example

Abstract: Background: Since the beginning of 2020, the Corona Virus Disease has broken out globally. This public health incident has had a great impact on the work and life of the public. Aim: Based on the event system theory, this article explored the influence of the “COVID-19” event on emotional exhaustion and deviant workplace behaviors. Methods: This survey’s objects are employees working in Tianjin, Beijing, Hebei affected by the epidemic. Using the questionnaire star, the online platform of the Marketing Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…In addition, it increases our understanding of COVID-19 pandemic criticality and empirically accounts for the advantages and disadvantages of COVID-19 pandemic criticality among the police workforce based on EST. While the COVID-19 pandemic has garnered much attention, its attributes have been largely neglected in research (Caldas et al, 2021;Liu et al, 2020Liu et al, , 2021Teng et al, 2020;Zhu et al, 2020). Our findings are consistent with some previous studies.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, it increases our understanding of COVID-19 pandemic criticality and empirically accounts for the advantages and disadvantages of COVID-19 pandemic criticality among the police workforce based on EST. While the COVID-19 pandemic has garnered much attention, its attributes have been largely neglected in research (Caldas et al, 2021;Liu et al, 2020Liu et al, , 2021Teng et al, 2020;Zhu et al, 2020). Our findings are consistent with some previous studies.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…The COVID-19 pandemic has proliferated worldwide and its strength varies. The different attributes of COVID-19 pandemic strength have influenced individuals' psychological and behavioral responses (Liu et al, 2020). Among these attributes, criticality refers to the impact of an entity's goals.…”
Section: Estmentioning
confidence: 99%
See 2 more Smart Citations
“…In this severe situation, the negative mental health of employees undoubtedly affects the quality of tasks, thereby affecting corporate performance and business sustainability [14,[63][64][65]. Sasaki et al [14] concluded that the fear of COVID-19 and psychological distress could affect work satisfaction and turnover intention.…”
Section: Individual Levelmentioning
confidence: 99%